Role of Superstition in Religious Practices - Gumber, Piyush (International Journal of Control and Automation, 2018)
Something held, partially held, or practiced when there seems to be no logical basis. Those that use the word do so in an arrogant manner, suggesting that they have special insight into scientific, philosophical, or theological matters. It's too vague to be useful in any context other than personal opinion. For this reason, we may broadly divide superstitions into three categories: religious, cultural, and individual.A Christian, for example, may think that if he opens the Bible at random and reads the passage that first catches his eye at a moment of crisis, he will be directed by the Bible. This is just one example of the way in which superstitions may collect as a peripheral belief system inside any religious tradition. Many people's religious practices are seen as superstitious by those of other faiths. For example, Constantine, the Roman emperor, dismissed non-Christian rituals as such, and Roman Historian Tacitus described Christianity as a "pernicious superstition." Many Protestants also view the Roman Catholic admiration of relics, images, and the saints with contempt. Last but not least, an atheist may see all religious acts as superstitious. The topic of superstition's place in religious rituals is at the heart of the current discussion.